A state health service
1937-07 1937 1930s 3 pages L.C.29/July, 1937. LABOUR PARTY LOCAL GOVERNMENT DEPARTMENT A STATE HEALTH SERVICE* PRIMARY CONSIDERATIONS At the present time, medical care is provided in four main forms - the private practitioner, the voluntary hospitals and other voluntary services, National Health Insurance, and the various Local Authority services, including the Poor Law. Assuming, for the purpose of this preliminary Report, that the aim should be a State Health Service, the first question to be decided is whether such a Service should be built (a) on National Health Insurance (by its extension to dependants, etc.), or (b) on the Local Authority Health Services. It is suggested that the proper course is the latter. NATIONAL HEALTH INSURANCE If this be accepted, it is difficult to maintain a separate panel system for insured persons, while at the same time uninsured persons and all dependants are provided for by the Local Authorities. Moreover, there are very grave deficiencies in the panel system, as regards both the type and standard of medical care provided and the existence of vested property interests in panels as such. A primary practical requirement, therefore, would be to take medical benefits away from Health Insurance altogether and to confine the Insurance Scheme to cash benefits only. If Health Insurance were confined to cash benefits, the following changes would have to be considered:- (a) Insurance contributions to be wholly devoted to cash benefits and their administration. (b) Rates of benefit as far as possible to correspond to the rates of Unemployment Insurance benefit at the time, but maternity cash benefit to continue to be paid. (c) Benefits to be at national standard rates, which would involve the complete pooling of contributions and of Approved Society funds. (d) Compulsory insurance to include manual workers as at present, without income limit, and for non-manual workers the maximum limit to be raised from £250 to, say, £300; any uninsured worker within the £500 limit to be eligible to join voluntarily at the ordinary combined rate of employer's and employee's contribution. 292/847/1/3